Menara Worldwide, Bukit Bintang - Rohaizam, Muhammad Mirza; Ahmat, Izhan Faezy; Ahmad Kamal, Nurtsuraiya Raihanah (2024)
Menara Worldwide, a distinguished 25-story office tower nestled in the vibrant heart of Kuala Lumpur's coveted Golden Triangle, proudly reflects the success story of Central Holdings Berhad (CHB). Established in 1969, CHB's transformative journey, particularly under the guidance of PKNS Real Estate Sdn Bhd (PREC), began a new chapter on December 27, 2013. This pivotal moment saw PREC acquiring the entire share from Worldwide Holdings Berhad, solidifying its ownership of CHB. While Menara Worldwide faced challenges during its inception, including a tumultuous decade marred by issues and setbacks, the tower has triumphed over adversity. Today, it stands as a testament to resilience, housing Premier Grade A Tier-1 brands such as Volvo, Lazada, Zalora, with a significant portion dedicated to AIG, its anchor tenant. The remarkable turnaround can be credited to the unwavering commitment of PKNS Real Estate Sdn Bhd, a company adept at implementing yield-boosting strategies.